Chondroitin sulfate alleviates osteoarthritis by upregulating HSPA8 to inhibit chondrocyte ferroptosis - Jiayang Jiang; Yangyang Xu; Tianming Dai; Junyan Chen; Siming Li; Qingqi Meng (PLoS ONE, 2026)
Osteoarthritis (OA) is a prevalent degenerative joint disease with no curative treatment currently available. Recent evidence suggests that chondrocyte ferroptosis contributes to OA progression. Chondroitin sulfate (CS), widely used in OA management, exhibits anti-inflammatory and antioxidant properties, yet its role in modulating ferroptosis remains unclear. In this study, we investigated whether CS alleviates OA by inhibiting chondrocyte ferroptosis and explored the underlying mechanisms. Using an in vitro ferroptosis model induced by RSL3 in rat chondrocytes, we found that CS significantly restored cell viability and ameliorated ferroptosis-related changes, including reduction of intracellular and mitochondrial ROS, lipid peroxidation, and iron overload. CS also downregulated the expression of ferroptosis markers PTGS2 and ACSL4, while upregulating SLC7A11 and HSPA8 in a dose-dependent manner. Network pharmacology and transcriptomic analysis identified HSPA8 as a key overlapping gene among CS targets, OA-related differentially expressed genes, and ferroptosis-related genes. In a rat OA model induced by modified Hulth surgery, CS treatment attenuated cartilage degradation, as evidenced by improved OARSI scores, restored COL2A1 expression, and suppressed MMP13. Immunohistochemistry confirmed that CS upregulated SLC7A11 and HSPA8 while downregulating ACSL4. These findings demonstrate that CS mitigates OA progression by inhibiting chondrocyte ferroptosis, potentially through upregulation of HSPA8 and subsequent enhancement of SLC7A11 expression. Our study provides novel insights into the mechanism of CS in OA treatment and highlights ferroptosis as a promising therapeutic target.